PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PAI - Nadjematul Faizah; Siti Rahmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
The problem in this research is about the low performance of PAI teachers. The purpose of this research is to find out the role of school principals in improving the performance of PAI teachers at MI At-Taufieq Jakarta and what hinders school principals from improving the performance of PAI teachers at MI At-Taufieq Jakarta. This study uses a qualitative approach with descriptive research methods, with data collection techniques through: Interviews, Observation and Documentation. Based on the results of the study it can be concluded that the MI AtTaufieq Jakarta principal carries out functions and roles according to competence as a school principal. The principal performs his role in improving teacher performance with work programs: focusing on curriculum development and teaching and learning activities in schools, developing the creativity of PAI teachers in teaching by making annual, semester and learning program plans and following the existing curriculum, namely the 2013 curriculum, fulfilling the need for facilities and infrastructure, and enforce discipline in the school environment by setting an example of being present on time during working hours. The implementation of the work program has been going quite well although there are still obstacles such as: constraints on meeting the needs of facilities and infrastructure, the teacher's closed attitude, and the uneven distribution of teacher expertise in using computers using the internet. The school principal is responsive to existing problems. The principal provides motivation by supervising the performance of PAI teachers directly and indirectly.